2016
DOI: 10.1002/ange.201608500
|View full text |Cite
|
Sign up to set email alerts
|

A Metallaanthracene and Derived Metallaanthraquinone

Abstract: Metalla‐analogues of archetypal aromatic molecules are attracting ever increasing interest. Although metallabenzenes (which fall within this class) have been well studied, fused‐ring metallabenzenes are rare and of the linear polycyclic metallaaromatic hydrocarbons, only metallanaphthalene is known. Herein we report the first metallaanthracene, [Ir(C13H8{CH2CO2Me‐5})Cl(PPh3)2]O3SCF3 (5), which represents the next member of this series of polycyclic compounds. Structurally, 5 has a number of features in common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…[1][2][3][4] It is noteworthy that such Mn-containing aromatic metallacycles remain unprecedented. [1][2][3][4] It is noteworthy that such Mn-containing aromatic metallacycles remain unprecedented.…”
Section: Aromaticity and Dft Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] It is noteworthy that such Mn-containing aromatic metallacycles remain unprecedented. [1][2][3][4] It is noteworthy that such Mn-containing aromatic metallacycles remain unprecedented.…”
Section: Aromaticity and Dft Analysismentioning
confidence: 99%
“…[1,2] Besides the most studied metallabenzenes and their derivatives,recent years have witnessed the emergence of structurally diversified metalla-aromatics. [1,2] Besides the most studied metallabenzenes and their derivatives,recent years have witnessed the emergence of structurally diversified metalla-aromatics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently,F rogleya nd Wright successfully prepared the first metallaanthracene complex, the iridaanthracene 1 (Scheme1), which can be considered as anovel polycyclic aromatic hydrocarbon including at ransition-metal fragment in its structure. [10] According to the available structurala nd spec-troscopic data, it is suggested that the transition-metal fragment inducesas ignificant influenceo nt he p-system of the molecule. Despite that, metallabenzene 1 readily undergoes aD iels-Alderr eaction with maleic anhydride in 1,2-dichloroethaneh eated at reflux to produce, after spontaneous loss of one proton, the correspondingn eutral fused-ring iridabenzofuran cycloadduct (Scheme 1).…”
Section: Introductionmentioning
confidence: 98%
“…Despite that, metallabenzene 1 readily undergoes aD iels-Alderr eaction with maleic anhydride in 1,2-dichloroethaneh eated at reflux to produce, after spontaneous loss of one proton, the correspondingn eutral fused-ring iridabenzofuran cycloadduct (Scheme 1). [10] Therefore,i nt erms of the Diels-Alder reactivity,t he novel iridaanthracene 1 seems to behave similarly to its all-carbonc ounterpart, anthracene, whichi sa lso able to produceas imilar cycloadduct in the presence of maleic anhydride. [11] Nevertheless,t he influenceo ft he transition-metal fragment on the reactivity of the system, compared with the parenta nthracene, is essentially unknown.…”
Section: Introductionmentioning
confidence: 99%